2018
DOI: 10.1016/j.foodcont.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of fresh-cut broccoli with a water–assisted UV-C technology and its combination with peroxyacetic acid

Abstract: The effectiveness of a water-assisted UV-C (WUV) technology for the decontamination of fresh-cut broccoli from conventional and organic agricultural practices was evaluated as an alternative to chlorine sanitation. Several WUV doses (0.3-1.8 kJ m-2) were tested alone or combined with peroxyacetic acid (PAA). Results showed that 0.5 kJ m-2 was sufficient to reduce natural total aerobic mesophilic microorganisms by 2 log 10 in conventional broccoli without 2 negative consequences on the physical quality. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
3
9
1
Order By: Relevance
“…In contrast, we observed no change in the headspace composition or in the chlorophylls contents in samples treated with WUV (0.5 kJ m -2 ) or PL (15 kJ m -2 ) compared to the water control during storage for 8 or 15 d, respectively. These results agreed with our previous results in this matrix (Collazo et al, 2018). In contrast, increased respiration and negative changes in color parameters were eventually observed in chlorine-treated samples, implying that both WUV and PL technologies contributed better to preserve color and overall quality than chlorine sanitation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, we observed no change in the headspace composition or in the chlorophylls contents in samples treated with WUV (0.5 kJ m -2 ) or PL (15 kJ m -2 ) compared to the water control during storage for 8 or 15 d, respectively. These results agreed with our previous results in this matrix (Collazo et al, 2018). In contrast, increased respiration and negative changes in color parameters were eventually observed in chlorine-treated samples, implying that both WUV and PL technologies contributed better to preserve color and overall quality than chlorine sanitation.…”
Section: Discussionsupporting
confidence: 92%
“…In fresh-cut broccoli, continuous UV-C at a dose of 8 kJ m -2 increased total antioxidant activity as well as phenolic compounds and ascorbic acid contents. We observed that total phenolic content was maintained after PL treatment compared to water-washing while it was reduced after chlorine sanitation as it was observed in previous experiments performed by our work group in fresh-cut broccoli using the same technology (Collazo et al, 2018). Furthermore, we observed and enhanced accumulation in total antioxidant capacity in PL-treated samples during the first 24 h, as measured by DPPH method, showing certain hormetic effect as has been previously reported in this commodity (Martínez-Hernández et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations